Effects of hyperkalaemia on the excitability of peripheral nerve - Seneviratne, K. N. (1972)
An experimental animal model has been developed for the study of excitability change in peripheral nerve during limb ischaemia. This model has been used to investigate the effects of hyperkalaemia on the sequence of excitability change that occurs during cuff-induced limb ischaemia and in the post-ischaemic recovery period. The results lend support to the hypothesis that the dynamics of K ion concentration in the periaxonal space play a critical role in determining these excitability changes and that the polyanionic mucopolysaccharide gap substance of the node of Ranvier is likely to constitute the diffusion barrier that defines the periaxonal space.